Impact of COVID-19 on in vivo work and patient sample availability for cancer research - Mulholland, EJ (Springer Nature, 2021)
The COVID-19 pandemic has destabilized the traditional bench to bedside workflow of cancer research. Particularly, in vivo experimentation plus the collection and distribution of patient samples has been significantly affected. Strategies are needed now to revolutionize current cancer research practices in order to avoid history repeating itself in future pandemics.